Chemoenzymatic access to (+)-artabotriol and its application in collective synthesis of (+)-grandiamide D, (-)-tulipalin B, (+)-spirathundiol, and (+)-artabotriolcaffeate - Batwal, Ramesh U.; N. P. Argade (Synthesis-Stuttgart, 2016)
Starting from dimethyl (+/-)-2-hydroxy-3-methylenesuccinnate chemoenzymatic collective formal/total synthesis of enantiomerically pure bioactive natural products has been described via the advanced level common precursor (+)-artabotriol. An efficient enzymatic resolution with high enantiomeric purity, selective diester to diol reduction, and requisite dehydrative coupling reactions without any racemization are the significant topographies.
Keywords: (+)-artabotriol; collective synthesis; coupling reactions; dimethyl (+/-)-2-hydroxy-3-methylenesuccinate; Enzymatic resolution; Natural products; reduction